Moral improvement (Islox al- Akhloq): revisiting the prophetic method in the midst of materialistic tendencies - Abdul Razak, Abdul Latif (Eubios Ethics Institute, 2010)
Moral improvement is defined as a change in behavior trait from bad to good, good to better and better to best. Nowadays, many programs are created and offered by psychologists, trainers and motivators to help people, especially the youth, in behavior modification. Expensive fees and ineffective modules are overshadowed with aggressive advertisements and exaggerated testimonies. The tendency of parents in expecting easy and fast positive changes in their children aggravates the situation. In many cases, the participants returned home with superficial and shortlived developments. This paper therefore aims at revisiting behavior modification method used by the Prophet (p.b.u.h) and sees how this prophetic method is able to produce successful people throughout history in the persons of Abdul Rahman bin Auf in business, Umar Abdul Aziz in governance and so on. It is hoped that this prophetic method can help our psychologists, trainers, motivators in preparing and reviving their modules, as well as parents in their relentless effort in improving their childrenʼs behavior.